The Effect of Antihypertensive Drugs on Blood Pressure in Preeclamptic Women at RSIA Ananda Makassar in 2020-2022 - Nurrohmah; Darmawansyih; Dewi Setiawati; Andi Sitti Rahma; Zulfahmi Alwi (International Journal of Health Engineering and Technology, 2025)
Background: The maternal mortality rate (MMR) in Indonesia is still very high, especially maternal mortality where in 2015 the maternal mortality rate (MMR) in Indonesia reached 305 per 100,000 live births caused by bleeding, infection and preeclampsia. This study aims to determine the effect of administering antihypertensive drugs on the blood pressure of preeclamptic mothers at RSIA Ananda Makassar in 2020-2022. Method: Quantitative research with a cross-sectional research design using a total sampling technique, where the number of samples is the same as the population. The samples in this study were mothers diagnosed with preeclampsia at the Ananda Mother and Child Hospital in Makassar, taking into account the inclusion and exclusion criteria. The number of samples in this study was 80 people. Result: Data analysis was carried out univariate and bivariate. Bivariate analysis of the effect of administering antihypertensive drugs on initial and discharge systolic blood pressure using the Wilcoxon test obtained a P-value <0.01 and for initial and discharge diastolic blood pressure a P-value <0.01 was obtained. Changes in decreasing systolic blood pressure using the Mann Whitney test obtained a P-value of <0.01 and diastolic blood pressure obtained a P-value of 0.027 Conclusion: There is an effect of administering antihypertensive drugs on the blood pressure of preeclamptic mothers at RSIA Ananda Makassar in 2020-2022